Pengaruh Motivasi Instrinsik dan Ekstrinsik Terhadap Produktivitas Karyawan Pada PT. Sinarindo Wiranusa Elektrik Bekasi - Putri Efliza, Sheira Angelina; Syarif, Mahmud (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Various factors, including work motivation, affect employee productivity, which is an important component of a company's success. An electronics manufacturing company PT. Sinarindo Wiranusa Elektrik in Bekasi became the subject of this study because of the importance of intrinsic and extrinsic motivation to increase employee productivity. with the aim of the study to determine how much influence intrinsic and extrinsic motivation have on employee productivity partially and simultaneously. This study was conducted quantitatively using analysis carried out through Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression, T Test, F Test, and Determination Coefficient with SPSS Version 25. Data were collected from 50 assembly division workers through observation, interviews, and Likert-scale questionnaires. The test results showed that the influence of intrinsic and extrinsic motivation on employee productivity was positive and significant (t-count = 3.094; p = 0.003 0.05). On the other hand, the influence of extrinsic motivation is not significant (t-count = 0.025; p = 0.980 0.05), with R-square of 0.236, indicating that the influence of both variables simultaneously contributes 23.6% of productivity variation. Thus, increasing employee productivity at PT. Sinarindo Wiranusa Elektrik is more dependent on increasing intrinsic motivation. Thus, intrinsic motivation is the dominant factor.